Pengembangan Program Pembelajaran Link and Match Melalui Penerapan Metode Sistem Ganda untuk Mendukung Revolusi Industri 4.0 Secara Sinergi Dengan Kebebasan Belajar - Fitri Mardhotillah Gumay; I Wayan Distrik; Agus Suyatna; Munadhirotul Azizah (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to describe a Link and Match program used on dual-system models that is valid, practical, and effective to support industrial revolution 4.0 in profile freedom to learn. This type of research is development research with the ADDIE development design which includes analyze, design, development, implementation, and evaluation. The data analysis technique uses a mixed method which combines qualitative and quantitative methods. The results showed that: The Link and Match program using a dual-system model is declared valid, including syllabus, RPP, e-LKPD and e-Handout whose learning process is designed to include activities that adapt to Indonesian national work competency standards (SKKNI Level II) by maximizing the use of various representation that can support the industrial revolution 4.0 with the profile of independent learning. The presentation of e-LKPD and e-Handouts has been adapted to the local wisdom competencies available in Lampung Province and the needs of students to study independently or in groups so that they can support the industrial revolution 4.0 with the profile of independent learning; The practicality of the Link and Match program using a dual-system model is reviewed based on student responses which include responses to the learning process, responses to e-LKPD and e-Handouts so that they can be used as a productive learning topic on Rubber Processing in SMK class XI semester odd; The effectiveness of the Link and Match program using a dual-system model is categorized as high which show that there is an average difference between the experimental class and the control class. The output of this development is the establishment of MoU (Memorandum of Understanding) with various DUDI in Lampung Province.